IMPLEMENTASI KURIKULUM KEPERAWATAN AIPNI 2021 BERBASIS FIKIH PADA MATA KULIAH PENDIDIKAN AGAMA ISLAM - Ma’muroh, Ma’muroh; Rohanah, Rohanah; Dora, Rafika; Yulia, Yulia; Dewi, Liza Puspa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study aims to analyze the implementation of the 2021 AIPNI Nursing Curriculum in Islamic Religious Education courses based on Islamic jurisprudence (Fikih) at STIKes Dharma Husada Tangerang. The background of this study is the importance of integrating Islamic values, especially Islamic jurisprudence, in shaping the spiritual competence and professional ethics of nursing students. The 2021 AIPNI Curriculum emphasizes an outcome-based education approach and professional character, thus requiring an implementative strategy in teaching Islamic religious courses that are relevant to clinical practice and the dynamics of medical ethics. This study uses a qualitative-descriptive approach with data collection techniques through classroom observation, RPS document studies, and semi-structured questionnaires and interviews with 34 students of the S1 Nursing Study Program in the odd semester of the 2024/2025 academic year. The results of the study indicate that the implementation of the curriculum has covered several aspects of practical fiqh that are directly related to the world of nursing, such as fiqh for caring for dying patients, ethics of interaction between the sexes, and the use of drugs in emergency conditions. However, obstacles were also found such as limited contextual teaching resources, the dominance of cognitive approaches, and the lack of collaboration between religious lecturers and nursing lecturers in compiling teaching materials. The conclusion of this study confirms that the implementation of Islamic Religious Education based on fiqh in the AIPNI curriculum has great potential to strengthen the spiritual integrity of nursing students, but requires strengthening in the aspects of methodology, content based on clinical case studies, and synergy between lecturers across fields. These findings are expected to be input in the development of a more holistic and Islamic higher health education curriculum. ABSTRAK Penelitian ini bertujuan untuk menganalisis implementasi Kurikulum Keperawatan AIPNI 2021 pada mata kuliah Pendidikan Agama Islam berbasis ilmu fikih di STIKes Dharma Husada Tangerang. Latar belakang penelitian ini adalah pentingnya integrasi nilai-nilai keislaman, khususnya fikih, dalam membentuk kompetensi spiritual dan etika profesional mahasiswa keperawatan. Kurikulum AIPNI 2021 menekankan pendekatan pembelajaran berbasis capaian (outcome-based education) dan karakter profesional, sehingga memerlukan strategi implementatif dalam pengajaran mata kuliah agama Islam yang relevan dengan praktik klinik dan dinamika etika medis. Penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan teknik pengumpulan data melalui observasi kelas, studi dokumen RPS, serta kuesioner dan wawancara semi-terstruktur kepada 34 mahasiswa Program Studi S1 Keperawatan semester ganjil tahun akademik 2024/2025. Hasil penelitian menunjukkan bahwa implementasi kurikulum telah mencakup beberapa aspek fikih praktis yang berkaitan langsung dengan dunia keperawatan, seperti fikih perawatan pasien sekarat, etika interaksi antar jenis kelamin, dan penggunaan obat-obatan dalam kondisi darurat. Namun, ditemukan pula hambatan seperti keterbatasan sumber ajar kontekstual, dominasi pendekatan kognitif, serta kurangnya kolaborasi antara dosen agama dan dosen keperawatan dalam penyusunan materi ajar. Simpulan dari penelitian ini menegaskan bahwa implementasi Pendidikan Agama Islam berbasis fikih dalam kurikulum AIPNI memiliki potensi besar untuk memperkuat integritas spiritual mahasiswa keperawatan, tetapi memerlukan penguatan pada aspek metodologi, konten berbasis studi kasus klinik, dan sinergi antar dosen lintas bidang. Temuan ini diharapkan dapat menjadi masukan dalam pengembangan kurikulum pendidikan tinggi kesehatan yang lebih holistik dan Islami.